Far-field autofluorescence nanoscopy. - Bierwagen, J; Testa, I; Fölling, J; Wenzel, D; Jakobs, S; Eggeling, C; Hell, S (2010)
We demonstrate far-field optical imaging at the nanoscale with unlabeled samples. Subdiffraction resolution images of autofluorescent samples are obtained by depleting the ground state of natural fluorophores by transferring them to a metastable dark state and simultaneously localizing those fluorophores that are transiently returning. Our approach is based on the insight that nanoscopy methods relying on stochastic single-molecule switching require only a single fluorescence on-off cycle to yield an image, a condition fulfilled by various biomolecules. The method is exemplified by recording label-free nanoscopy images of thylakoid membranes of spinach chloroplasts.